Reactive power control to enhance the VSC-HVDC system performance under faulty and normal conditions - Mohamed S. Ghayad; Niveen M. Badra; Almoataz Y. Abdelaziz; Mahmoud A. Attia (Institute of Advanced Engineering and Science, 2019)
This paper studied the reactive power control of the voltage source converters based high-voltage direct current system (VSC-HVDC). PI (proportional & integration) controller was used in this work to enhance the dynamic response of the system. Gravitational search algorithm (GSA) and sine cosine algorithm (SCA) are used to get optimal parameters of the PI controller. GSA algorithm is based on the gravity law for Newton while SCA depends on mathematical model based on cosine and sine functions. These algorithms have an efficient global Search capability. The VSC-HVDC is exposed to different disturbances for checking the controller robustness. First disturbance was applying three phase faults on the system. While the second one was applying a step change in AC voltage. Finally, Applying step change in regulators reference values. Simulation results proved the controller superiority also verified the enhancement of the system dynamic response.